2009
DOI: 10.1179/174328109x443338
|View full text |Cite
|
Sign up to set email alerts
|

A static approach towards coke collapse modelling in blast furnace

Abstract: Burden distribution control in a blast furnace has a close relationship with wind acceptance and gas utilisation. Quantification of radial distribution of ore and coke is important for proper control of blast furnace operation. Charging of metallic burden over a layer of coke causes a portion of the coke layer to get dislodged from its original position, similar to the situation observed when a heavy material is dropped on a bed of lighter particles. This phenomenon, designated 'coke collapse', significantly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…It also provides the basic boundary information to study the burden descent and associated phenomena in the BF body. For a long time, such prediction has mainly relied on the models derived from the motion of a single particle or particle assembly . In recent years, the DEM approach, which considers all individual particles and their interaction with each other, has become a promising tool to guide burden charging operation …”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also provides the basic boundary information to study the burden descent and associated phenomena in the BF body. For a long time, such prediction has mainly relied on the models derived from the motion of a single particle or particle assembly . In recent years, the DEM approach, which considers all individual particles and their interaction with each other, has become a promising tool to guide burden charging operation …”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%
“…For a long time, such prediction has mainly relied on the models derived from the motion of a single particle or particle assembly. [121][122][123][124] In recent years, the DEM approach, which considers all individual particles and their interaction with each other, has become a promising tool to guide burden charging operation. [79,125] Figure 11 shows a representative application of DEM in simulating the bell-less charging system mainly used in modern BFs.…”
Section: Top Burden Charging Systemmentioning
confidence: 99%
“…In the past decades, substantial experiments and numerical studies have been conducted, focusing on various aspects of burden distribution, including falling trajectory of burden materials from the charging device onto the burden surface, development of the burden profile at the throat, coke collapse towards the center of the furnace under the influence of ore charging onto the coke layer, size segregation, descent of burden layers, and shaft thermal conditions relevant to heat transfer behavior and gas distribution . In particular, the discrete element method (DEM) is a typical approach which can capture motions of individual particles, hence particle flow behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the discrete element method (DEM) is a typical approach which can capture motions of individual particles, hence particle flow behavior. Such an approach has been extensively used to study burden distribution phenomena . For example, Ho et al investigated the effects of different parameters on gouge formation, and showed that burden distribution is affected by particle density, size, chute angle, and distance between the bin and chute.…”
Section: Introductionmentioning
confidence: 99%
“…This is a complication as the profile may vary strongly depending on the charging program. Some authors [17][18][19] have utilized the stability theory of slopes to determine if a layer would be stable upon charging a pellet layer. This is based on stability theory used extensively in geological applications and dam constructions.…”
Section: Introductionmentioning
confidence: 99%